2021
DOI: 10.1001/jamanetworkopen.2021.25538
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Characteristics of Deaths From Drug Overdose Before vs During the COVID-19 Pandemic in Rhode Island

Abstract: Key Points Question Were there changes in the rate and characteristics of deaths from drug overdose before vs during the COVID-19 pandemic in Rhode Island? Findings In this population-based cohort study of 470 adults who died of drug overdose in Rhode Island from January 1 to August 31 in 2019 and 2020, rates of death from overdose among men, deaths involving synthetic opioids, and deaths occurring in personal residences increased significantly in 2020 comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 63 publications
3
38
1
1
Order By: Relevance
“…The pattern of increase agrees with studies of overdose mortality in other regions. 53 , 54 There are distinct pathways by which the pandemic may influence substance use-related mortality, despite the lack of increase in suicide deaths. Unlike suicide, substance use can also serve as a coping mechanism for psychosocial stressors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pattern of increase agrees with studies of overdose mortality in other regions. 53 , 54 There are distinct pathways by which the pandemic may influence substance use-related mortality, despite the lack of increase in suicide deaths. Unlike suicide, substance use can also serve as a coping mechanism for psychosocial stressors.…”
Section: Discussionmentioning
confidence: 99%
“… 55 Joblessness among low wage earners is suspected to play a role in higher rates of opioid overdoses during the pandemic. 53 , 56 In the past, economic downturns were also associated with increased numbers of opioid overdose deaths— particularly in white men under the age of 45—and macro-economic conditions drive opioid related deaths. 15 Long-term unemployment is also a risk factor for overdose-related deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Recent statistics show a 38.4% increase in opioid-related deaths from June 2019 to May 2020, 4 and state-level data have linked stressors of the COVID-19 pandemic to surge in fatal overdoses. 5 Literature suggests the opioid crisis has been escalated by a lack of access to drug screening and treatment for opioid use disorder (OUD) due to care disruption by the COVID-19 pandemic. 6 Ongoing opioid addiction prevention efforts have also been disrupted by social distancing practices and isolation that can contribute to the misuse of prescription or illicit opioids.…”
Section: Introductionmentioning
confidence: 99%
“…Addiction services and treatment options were also severely limited to align with new social distancing norms. Recent reports now confirm that drug overdose deaths increased during the COVID-19 pandemic [196][197][198][199]. Wang et al recently reported that persons with SUD were at significantly increased risk for COVID-19 and worse outcomes [200].…”
Section: Drugs Of Abuse and Sars-cov-2mentioning
confidence: 91%